Implementation of IEC 61499 and Model Checking for Drill Simulator - Izza Ainaa M. Ridza, Nur; Alwi, Saifulza (International Journal of Engineering and Technology, 2018)
Reusability of control codes is one of the basic angles in mechanical robotization, especially for the advancement of high dependable control frameworks. In this paper, we examine a general structure and usage of IEC 61499 standard that can be utilized to speak to conveyed control frameworks and rebuilding the control programs. This paper likewise expects to change the current IEC 61131 based model of computerization framework into the models that pursues IEC 61499 standard. We utilize a bore test system as precedent by mimicking the model utilizing Function Block Development Kit (FBDK) in light of IEC 61499. Accordingly, a piece of the control codes can be used for reusable reason to accomplish framework control objective.Â Â